2020
DOI: 10.1016/j.disc.2019.111605
|View full text |Cite
|
Sign up to set email alerts
|

Improved bound for the dimension of posets of treewidth two

Abstract: Joret et al. proved that posets with cover graphs of treewidth at most 2 have dimension at most 1276. Their proof is long and very complex. We give a short and much simpler proof that the dimension of such posets is at most 12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The first major result linking dimension with structural graph theory is due to Joret, Micek, Milans, Trotter, Walczak and Wang [7], who showed that for each pair (t, h) of positive integers, there is a least positive integer d(t, h) so that if P is a poset of height h and the tree-width 1 of the cover graph of P is t, then dim Recently, Seweryn [13] has given the following substantive improvement:…”
Section: Structural Graph Theorymentioning
confidence: 99%
“…The first major result linking dimension with structural graph theory is due to Joret, Micek, Milans, Trotter, Walczak and Wang [7], who showed that for each pair (t, h) of positive integers, there is a least positive integer d(t, h) so that if P is a poset of height h and the tree-width 1 of the cover graph of P is t, then dim Recently, Seweryn [13] has given the following substantive improvement:…”
Section: Structural Graph Theorymentioning
confidence: 99%
“…Generally, in the past 15 years alone, more than 25 published research papers have explored connections between dimension and graph theoretic properties of cover graphs and order diagrams (we list some of them: outerplanarity [3,5], planarity [18,13,1,10], cut-vertices structure [22], treewidth [17,9], exclusion of some structures [25,15,6,7], or even more complex structural parameters [11,8]). For our considerations, it is worth mentioning a result in [9].…”
Section: Introductionmentioning
confidence: 99%